Individualized Chemotherapy in Advanced NSCLC Patients Based on mRNA Levels of BRCA1 and RRM1 - Ren, Sheng-xiang; Li, Ai-wu; Zhou, Song-wen; Zhang, Ling; Wang, Yong-sheng; Li, Bing; Chen, Xiao-xia; Zhang, Jie; Xu, Jian-fang; Zhou, Cai-cun (Chinese Journal of Cancer Research; Vol 24, No 3 (September 01, 2012): Chinese Journal of Cancer Research, 2012)
Objective: Experimental evidence suggests that the overexpression of breast cancer-specific tumor suppressor protein 1 (BRCA1) gene enhances sensitivity to docetaxel and resistance to cisplatin and ribonucleotide reductase M1 (RRM1) gene overexpression enhances resistance to gemcitabine. To further examine the effect of BRCA1 and RRM1/> mRNA levels on outcome in advanced non-small cell lung cancer (NSCLC), we performed this non-randomized phase II clinical trial which tested the hypothesis that customized therapy would confer improved outcome over noncustomized therapy. Methods: RNA was isolated from fresh tumor tissue. Patients received chemotherapy regimen based on their BRCA1 and RRM1 mRNA levels: both low–cisplatin plus gemcitabine (GP); both high–vinorelbine plus cisplatin (NP); BRCA1 low and RRM1 high–cisplatin plus docetaxel (TP); BRCA1 high and RRM1 low–vinorelbine plus gemcitabine (GN). Results: From Dec 2005 to Nov 2008, 94 metastatic and locally advanced NSCLC patients from our institute were enrolled in this study. The median age was 58 years old. Among them, 21 patients received GP, 30 patients received TP and 43 patients received NP chemotherapy. GP group had a higher response rate, and longer median time to progression (TTP) and median overall survival (OS) time than the other 2 groups. The response rates in the GP, TP and NP groups were 42.9%, 36.7% and 27.9%, respectively (P=0.568). The median TTP was 5.6, 5.0, 4.8 months (P=0.975), respectively, and the median OS time was 12.5, 11.0, 9.7 months (P=0.808), respectively. Conclusion: Chemotherapy customized according to BRCA1 and RRM1 expression levels is associated with higher response rate and longer TTP and OS time in the GP group. This suggests that BRCA1 and RRM1 mRNA levels could be used as biomarkers in individual therapy in NSCLC.